2018
DOI: 10.1093/infdis/jiy133
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, Immunogenicity, and Safety of a 9-Valent Human Papillomavirus Vaccine: Subgroup Analysis of Participants From Asian Countries

Abstract: The 9vHPV vaccine was efficacious, immunogenic, and well-tolerated in Asian participants from 2 international, randomized clinical trials. Data support 9vHPV vaccination programs in Asia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 44 publications
3
15
0
Order By: Relevance
“…In previous 4vHPV vaccine clinical trials, rates of injection-site AEs were 64% and 60% in Japanese boys and men, respectively, while geometric mean titer ratios (boys versus men) for anti-HPV6/11/16/18 antibodies were 1.25–3.05 [ 30 , 31 ]. Similar results were observed in studies of the 9vHPV vaccine in Japanese girls and women [ 32 , 33 ]. Most injection-site AEs were mild and moderate in both girls and young women in Study 027 and 028, and participants recovered within 5 days; these results were also consistent with the severity and duration of reactions observed in Japanese boys and men receiving the 4vHPV vaccine, as well as Japanese girls and women given the 9vHPV vaccine [ [30] , [31] , [32] , [33] ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In previous 4vHPV vaccine clinical trials, rates of injection-site AEs were 64% and 60% in Japanese boys and men, respectively, while geometric mean titer ratios (boys versus men) for anti-HPV6/11/16/18 antibodies were 1.25–3.05 [ 30 , 31 ]. Similar results were observed in studies of the 9vHPV vaccine in Japanese girls and women [ 32 , 33 ]. Most injection-site AEs were mild and moderate in both girls and young women in Study 027 and 028, and participants recovered within 5 days; these results were also consistent with the severity and duration of reactions observed in Japanese boys and men receiving the 4vHPV vaccine, as well as Japanese girls and women given the 9vHPV vaccine [ [30] , [31] , [32] , [33] ].…”
Section: Discussionsupporting
confidence: 89%
“…Similar results were observed in studies of the 9vHPV vaccine in Japanese girls and women [ 32 , 33 ]. Most injection-site AEs were mild and moderate in both girls and young women in Study 027 and 028, and participants recovered within 5 days; these results were also consistent with the severity and duration of reactions observed in Japanese boys and men receiving the 4vHPV vaccine, as well as Japanese girls and women given the 9vHPV vaccine [ [30] , [31] , [32] , [33] ]. An early onset of injection-site AEs was also observed in the placebo group, with most AEs occurring on the day of vaccination.…”
Section: Discussionsupporting
confidence: 89%
“…The currently available HPV vaccines are estimated to prevent 70–90% of cervical cancer cases [ 49 ]. The nonavalent HPV vaccine has been highly effective in preventing HPV infection and cancer diseases, with efficacies ranging between 90% and 100% [ 15 , 50 , 51 , 52 ]. A study reported by Garland and colleagues (2018) in Asian women showed that nonavalent significantly decreased the risk of persistent infection, abnormal cytology, and diseases caused by specific HPV types targeted by this vaccine [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The nonavalent HPV vaccine has been highly effective in preventing HPV infection and cancer diseases, with efficacies ranging between 90% and 100% [ 15 , 50 , 51 , 52 ]. A study reported by Garland and colleagues (2018) in Asian women showed that nonavalent significantly decreased the risk of persistent infection, abnormal cytology, and diseases caused by specific HPV types targeted by this vaccine [ 50 ]. In the present study, HPV vaccines could protect 20–69.0% of CIN2/3 cases in women with or without HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…The burden of cervical cancer and risk is different across populations around the world. Subgroup analyses from two Phase III double-blind randomized controlled trials were performed among Asian and Latin American participants to determine the population-specific vaccine efficacy 44,45. Similar high vaccine efficacy (>96%) against any grade of cervical, vulvar, and vaginal diseases, as well as greater than 93% against six-month persistent HPV infection, were found for both ethnic populations in individuals who were not infected with HPV.…”
Section: Vaccine Efficacy Of 9vhpvmentioning
confidence: 98%